The institutional construction of ethnicity: anthropology of the Nagas (The South Asianist Journal, 2014)
The indigenous world of Naga tribes has come to the attention through colonial ethnographies, census documentation and itineraries developed by early travel writers, botanists, foot soldiers, surveyors, tea planters and later hill administrators. Anthropological knowledge in this part of colonial India grew out of the need to control the “savage other” through imposition of “house tax” and “forced labour” that restricted their “autonomy”. This mechanism of political control was not strictly obligatory for the Nagas. Instead the hill administration worked hand in hand with the village headmen and local go between (dobashis) to establish patronage and rule of law. As Bernard Cohen (1996) has attentively argued, the administrative-ethnographic discourse was a crucial cultural technology of ruler. For the administrator-ethnographers the natives of the Naga Hills represented primitive societies almost untouched by (Western, Buddhist or Hindu) Civilizations. Jhum cultivation or slash and burn farming, head hunting rituals and slave trade practices became a key part of the colonial strategy to caricature the Nagas as savage and hedonistic. The imperial project of administering the frontier was thus justified. Textual and visual documentation of the Naga tribes gave literal and symbolic meaning to these portrayals. It led to ethic classification – ‘ethnic involution’ or ‘ethno genesis’ (Van Schendel 1992, Sumit Guha 1999) of the Nagas – social differentiation of hill people from the plains.